2019
DOI: 10.1159/000497279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E-Cadherin and β-Catenin as Prognostic Factor in Renal Cell Carcinoma with Tumor Thrombus of the Vena Cava

Abstract: Purpose: Renal cell carcinoma (RCC) forming tumor thrombus (TT) of vena cava (VC) is characterized by poor prognosis. Nevertheless, the outcome of patients after radical surgery varies. To date only limited data concerning prognostic biomarkers in this RCC subgroup are available. Methods: Out of 159 patients with pT3b/c RCC, 95 patients without synchronous distant metastases at time of diagnosis were included in the study cohort. After immunohistochemical (IHC) evaluation of E-cadherin and β-Catenin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The study suggests that an abnormal expression of E-cadherin in CC tissues is highly correlated with the pathological features of invasion and migration of cervical malignant tumors, and it can be used for the prognosis and evaluation of CC. Results of multiple studies have indicated that downregulation of E-cadherin expression promoted lymph node metastasis ( 27 , 28 ). Although results of some studies have indicated that downregulation of E-cadherin expression is associated with lymph node metastasis, there is no correlation between them, as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that an abnormal expression of E-cadherin in CC tissues is highly correlated with the pathological features of invasion and migration of cervical malignant tumors, and it can be used for the prognosis and evaluation of CC. Results of multiple studies have indicated that downregulation of E-cadherin expression promoted lymph node metastasis ( 27 , 28 ). Although results of some studies have indicated that downregulation of E-cadherin expression is associated with lymph node metastasis, there is no correlation between them, as assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although constituting a high-risk setting in general, there still is substantial clinical heterogeneity within the ccRCC IVC subgroup—with reported 5-year survival rates ranging from 37% to 65% for non-metastasized patients treated with nephrectomy in combination with tumor thrombectomy [ 4 , 5 , 6 , 7 , 8 , 9 ]. Regarding this discrepancy, biomarkers are urgently needed to identify patients with a specifically high risk of cancer relapse [ 10 , 11 ]. Potentially, ccRCC IVC patients may also benefit from adjuvant systemic therapy and an intensified follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…While constituting a high-risk setting in general, there still is substantial clinical heterogeneity within the ccRCC IVC subgroup – with reported 5-year survival rates ranging from 37 % to 65 % for non-metastasized patients treated with nephrectomy and tumor thrombectomy [4]–[9]. Regarding this discrepancy, biomarkers are urgently needed to identify patients with a specifically high risk of cancer relapse [10], [11]. Potentially, this subgroup of ccRCC IVC patients may also benefit from adjuvant systemic therapy and additional follow-up examinations.…”
Section: Introductionmentioning
confidence: 99%